The Influence of Financial Performance and Company Size on Company Value with Disclosure of Corporate Social Responsibility as a Moderating Variable - Kampo, Kunradus; Tangke, Paulus; Gosal, Kirey (Contemporary Journal on Business and Accounting, 2024)
Purpose – The purpose of this study was to examine the effect of financial performance and firm size on firm value and the moderating role of corporate social responsibility on the effect of financial performance and firm size on firm value. Design/methodology/approach – The research method uses moderated regression analysis to analyze the effect of corporate social responsibility in the relationship between the dependent and independent variables. Findings – The results of this study indicate that financial performance has a positive and insignificant effect on firm value. Firm size has a negative and insignificant effect on firm value. Corporate social responsibility is able to moderate the effect of financial performance and firm size on firm value. Originality – The sample companies are non-financial companies listed on the IDX for the period 2017-2019 which disclose annual reports and sustainability reports respectively, so that the total sample obtained covering 3 years is 39 samples. Keywords: Financial Performance, Company Size, Value Company, Corporate Social Responsibility, Signal Theory, Stakeholder Theory Paper Type Research Result